Globalisation with a Human Face and the Role of the United Nations - Lénárd Sándor (Poredbeno Pomorsko Pravo)
A large portion of modern-day human rights challenges stems from non-typical situations such as economic and financial crises, or environmental degradation. The rise of globalisation that goes hand in hand with the increasing impacts of business operations on people´s lives and their basic needs, from clean water to communication, certainly adds to this list. The regulatory model offered by the ˝Washington Consensus˝ has further fuelled this phenomenon. The utility provider who violates the right to water, the mining or extraction operations that endanger the right to health, or the digital platform that infringes on the freedom of speech and information all have detrimental impacts on the enjoyment of human rights. The paper explores this human rights challenge along with the historical path of international legal regulation, as well as the current regulatory attempts and treaty-making process to clarify State duty to protect human rights and responsibility in the context of business and human rights.